Integration of the Historical Values of the Youth Pledge in Civic Education Learning: A Strategy for Forming a Nationalist Spirit in Elementary School Students - Alma, Nur Alfiani; Rangkuti, Adinda Rahmah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This study examines the integration of the historical values of the Youth Pledge in Pancasila and Citizenship Education (PPKn) learning at an elementary Islamic school (MI) in Kendari City, with a focus on fostering students' nationalist spirit. The purpose of this study is to explore learning strategies that can build national awareness through the historical values of the Youth Pledge. The method used is a qualitative research with a case study approach, involving observation, interviews, and documentation in the PPKn MI class. The results show that the integration of the historical values of the Youth Pledge in PPKn learning contributes significantly to increasing students' national awareness and national identity. This approach successfully builds students' understanding of the importance of unity in diversity and increases their sense of social responsibility towards the nation. Consequently, the integration of these historical values enriches civic learning practices, encourages more contextual character education, and contributes to the formation of a more nationalistic and tolerant generation. This study also proposes the development of a more flexible and adaptive curriculum to optimize students' understanding of national values.